ANALISIS POTENSI DAN DAYA TARIK OBYEK WISATA PANTAI SALIPER ATE KABUPATEN SUMBAWA - Subhan Purwadinata; Ambarwati Ambarwati (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine the potential and attractiveness of the tourist object of Saliper Ate Beach in Sumbawa Regency. This research is a descriptive research that aims to describe the potential and attractiveness contained in the tourist object of Saliper Ate Beach in Sumbawa Regency. The type of data used is quantitative data in the form of answers from research informants obtained directly through the questionnaires given. Data collection methods are through observation, questionnaires and documentation. The analytical method used were the scoring method based on the Object Operation Area Analysis Guidelines and Nature Tourism Attraction (ADO-ODTWA) by the Director General of PHKA in 2003. The results of the study showed that the Saliper Ate beach tourism object has great potential tourism to be developed and has the opportunity to be tourist destination because it has tourist attraction, accessibility and supporting facilities and infrastructure. It was based on the results of assessment of the ADO-ODTWA guidelines with the value of the attractiveness criteria was 720, the value of accessibility criteria was 425 and supporting facilities and infrastructure in tourism object with value of 180. Thus, it was obtained that average value of Saliper Ate potency was 441,6 and was categorized as quite potential to be developed.